Informed consent for controlled human infection studies in low‐ and middle‐income countries: Ethical challenges and proposed solutions. (10th August 2020) - Vaswani, Vina; Saxena, Abha; Shah, Seema K.; Palacios, Ricardo; Rid, Annette
Abstract: In controlled human infection studies (CHIs), participants are deliberately exposed to infectious agents in order to better understand the mechanism of infection or disease and test therapies or vaccines. While most CHIs have been conducted in high‐income countries, CHIs have recently been expanding into low‐ and middle‐income countries (LMICs). One potential ethical concern about this expansion is the challenge of obtaining the voluntary informed consent of participants, especially those who may not be literate or have limited education. In some CHIs in LMICs, researchers have attempted to address this potential concern by limiting access to literate or educated populations. In this paper, we argue that this practice is unjustified, as it does not increase the chances of obtaining valid informed consent and therefore unfairly excludes illiterate populations and populations with lower education. Instead, we recommend that investigators improve the informed consent process by drawing on existing data on obtaining informed consent in these populations and interventions aimed at improving their understanding. Based on a literature review, we provide concrete suggestions for how to follow this recommendation and ensure that populations with lower literacy or education are given a fair opportunity to protect their rights and interests in the informed consent process.